Development of inclusive practice – the art of balancing emotional support and constructive feedback - Øen, Kristian; Krumsvik, Rune J.; Skaar, Øystein O. (Frontiers in Education, 2024)
Inclusive education in the context of challenging behaviour is one of the most demanding challenges for teachers. Good support systems help teachers become more positive about inclusion and gain greater confidence in realizing that they can succeed. Such support can be provided in the form of emotional support, internal or external guidance, courses, discussions or further education. As an alternative to a traditional individual-oriented approach to inclusion, this article argues that development of inclusive practice requires collaborative learning in the professional community, which again means that teachers have to make their own practice more transparent so that it can be explained, explored and challenged. This article is based on a qualitatively driven mixed-method case design, and the data come from interviews with and observations of 10 teachers, as well as a survey conducted at 16 schools in Western Norway. The findings show that many teachers struggle to find a balance between emotional support and asking exploratory questions about their schools' and their colleagues' practices. At the same time, it seems that schools that systematically ask each other critical questions have cultures that are more strongly characterized by a high degree of psychological safety and high professional standards.